Iron and Liver Diseases - Silvia Fargion; Michela Mattioli; Anna Ludovica Fracanzani; Gemino Fiorelli (Canadian Journal of Gastroenterology)
A mild to moderate iron excess is found in patients with liver diseases apparently unrelated to genetic hemochromatosis. Iron appears to affect the natural history of hepatitis C virus-related chronic liver diseases, alcoholic liver disease and nonalcoholic steatohepatitis by leading to a more severe fibrosis and thus aiding the evolution to cirrhosis.Ahigher frequency of mutations of the HFE gene, the gene responsible for hereditary hemochromatosis, is found in patients with liver diseases and increased liver iron than in normal patients. Patients with excess iron are potentially at a higher risk of developing hepatocellular carcinoma. Iron depletion therapy could interfere with fibrosis development and possibly reduce the risk of liver cancer occurrence.